U-Pb Zircon dating of upper cretaceous siliciclastic rocks from the Tanjero Flysch, NE Iraq: New constraints on their provenance and tectonic evolution - Nabaz Hama Aziz; Sadiq D.M (Kuwait Journal of Science)
The Tanjero flysch basin is located in the periphery of Qulqula Rise “accretionary complex terrane” of the Iraqi segment of the North Zagros Thrust Zone, marking the transition from passive margin to the accretionary complex terrane– flexural foreland basins setting. Based on Quartz-Feldspar-Rock fragment plot, the Tanjero clastics were classified as lithic arenites and feldspathic litharenites. The lithic fragments commonly consist of sedimentary (i.e. limestone and chert), volcanic and plutonic, and low-grade metamorphic rocks. Detrital zircon (DZ) U-Pb geochronology was used to characterise Upper Cretaceous siliciclastic rocks from the Tanjero Flysch, NE Iraq. Representative DZ U-Pb measurements revealed that the Tanjero Flysch clastics can be recycled many times in sedimentary systems whilst retaining robust U-Pb crystallisation ages during weathering, erosion, transport, deposition, diagenesis and low-grade metamorphism. The youngest zircon age population in the Tanjero Flysch yielded an age of 93-94 Ma which coincides closely with an Albian-Cenomanian arc -dominated magmatic event (i.e. 106–92 Ma). In addition the DZ U-Pb showed a strongly episodic age distribution 398- 448, 511-570, 646-690, 779, 878-880, 910-996 and 1045-1181 Ma  that suggests multicycled derivation mostly from the Neoproterozoic basement of the Arabian-Nubian Shield that were at some point hosted by the Early Pliensbachian-Turonian Qulqula Radiolarite Basin which was located along the Arabian passive margin.